Age at Arrival, English Proficiency, and Social Assimilation Among U.S. Immigrants - Hoyt Bleakley; Aimee Chin (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
Are U.S. immigrants' English proficiency and social outcomes the result of their cultural preferences, or of more fundamental constraints? Using 2000 Census microdata, we relate immigrants' marriage, fertility and residential location variables to their age at arrival in the U.S., and in particular whether that age fell within the "critical period" of language acquisition. We interpret the differences between younger and older arrivers as effects of English-language skills and construct an instrumental variable for English-language skills. Two-stage-least-squares estimates suggest that English proficiency increases the likelihood of divorce and intermarriage. It decreases fertility and, for some groups, ethnic enclave residence.
Keywords: J24; J12; J13; J61; 330